2005
DOI: 10.1103/physrevb.72.205124
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-selective Mott transition in multiband systems: Slave-spin representation and dynamical mean-field theory

Abstract: We examine whether the Mott transition of a half-filled, two-orbital Hubbard model with unequal bandwidths occurs simultaneously for both bands or whether it is a two-stage process in which the orbital with narrower bandwith localizes first (giving rise to an intermediate 'orbital-selective' Mott phase). This question is addressed using both dynamical mean-field theory, and a representation of fermion operators in terms of slave quantum spins, followed by a mean-field approximation (similar in spirit to a Gutz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
285
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(307 citation statements)
references
References 31 publications
19
285
3
Order By: Relevance
“…[2][3][4]. Specifically these papers introduced a separate slave spin for each orbital and considered mean field states where the slave spins associated with some orbitals were disordered while other slave spins stay ordered.…”
Section: Multiband Systems: Orbital Selective Orthogonal Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]. Specifically these papers introduced a separate slave spin for each orbital and considered mean field states where the slave spins associated with some orbitals were disordered while other slave spins stay ordered.…”
Section: Multiband Systems: Orbital Selective Orthogonal Metalsmentioning
confidence: 99%
“…Unlike the more traditional 'slave boson' representations, which have a U(1) gauge redundancy, and hence require introducing a compact U(1) gauge field 7 , the slave spin representation has only a Z 2 gauge redundancy. A 'slave spin representation' of this type was first introduced to study the multi-orbital Hubbard model [2][3][4][5] and the possibility of orbital selective Mott transitions in such models. The slave spin formulation has gained in popularity over the last few years, and has been employed to describe correlation effects in multiband metals such as the iron pnictides, and also to investigate non-equilibirum physics in quantum quenches 6 .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…29 We also note that since the original discussion of multiband Hubbard models of Ref. 3, many other studies have emerged where the slave-spin mean field has been employed and found regions of parameter space where the slave spins are disordered. We have emphasized that these should be interpreted as orthogonal metals or orbitally selective orthogonal metals.…”
Section: Realizing An Orthogonal Metalmentioning
confidence: 99%
“…[3][4][5], the disordering of the slave spin of some orbital signals a fractionalization of the electrons corresponding to that orbital into a charged fermion and a gapped Ising variable. The resulting charged fermion continues to be gapless and contributes to thermodynamics and transport just as in a Fermi liquid.…”
mentioning
confidence: 99%
See 1 more Smart Citation